E agora, juiz? : o poder judiciário entre uma constituição utópica e uma sociedade distópica - Rebouças, Glauber Dantas (2020)
The dissertation is premised on the utopian nature of constitutional norms and their purpose of conforming society to the values of solidarity, fraternity and dignity of the human person. Notwithstanding this constitutional design, there is a tendency for dystopia in Brazilian society, with an alarming number of homicides, embezzlement of public money through the practice of corruption, in addition to legislative changes that have challenged social rights, such as EC 95 / 2016 (from the ceiling of public spending), the labor reform (Law 13,467 / 2017) and the EC 103/2019 (pension reform). Thus, it is noted a deviation from the path indicated by the constituent legislator, making it imperative to question what should be the attitude of the members of the judiciary in the face of the mismatch between the ideology of nation outlined in the Constitution and the reality of violence, inequalities and exclusion that presents itself. A brief history of the Judiciary in Brazil, its role in the constitutional order of 1988, will be raised, arguing that the position of the judge must be of commitment to the founding values of the Federative Republic of Brazil, imposing, if necessary, the necessary restraints on the reforming impulses of the other powers, especially when they violate fundamental rights and guarantees. For this purpose, the hypothetical-deductive method will be used, based on bibliographic research on specialized doctrine, consultation of jurisprudence and websites.